2001
DOI: 10.1111/1469-8986.3810114
|View full text |Cite
|
Sign up to set email alerts
|

An early electrophysiological sign of semantic processing in basal extrastriate areas

Abstract: Recognition potential (RP), a recently discovered electrophysiological response of the brain, is sensitive to semantic aspects of stimuli. Given its peak values (about 250 ms), RP may be a good candidate for the study of semantic processing during its occurrence. However, its topography and neural generators are largely unknown. To improve this state of affairs, high-resolution electroencephalography and brain electrical source analysis were carried out. Results suggest a possible origin of RP in the lingual g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 59 publications
7
37
2
Order By: Relevance
“…Furthermore, similar topographical distribution for animate and inanimate objects could indicate similar neural substrate of processing these two categories, which is again in accordance with Tyler et al (2003) claiming that the same semantic system is active regardless of the categories processed. Our results are also in accordance with the results of Hinojosa et al (2001) who found, by applying the ERP technique, differences in latencies and amplitudes of the recognition potential (RP) between animals and objects as sensitivity to early visual categorization processing (Martín-Loeches et al 2001). They also found no differences either in ERP amplitudes and latencies or in a topographical distribution between these categories.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, similar topographical distribution for animate and inanimate objects could indicate similar neural substrate of processing these two categories, which is again in accordance with Tyler et al (2003) claiming that the same semantic system is active regardless of the categories processed. Our results are also in accordance with the results of Hinojosa et al (2001) who found, by applying the ERP technique, differences in latencies and amplitudes of the recognition potential (RP) between animals and objects as sensitivity to early visual categorization processing (Martín-Loeches et al 2001). They also found no differences either in ERP amplitudes and latencies or in a topographical distribution between these categories.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the confluence of certain manipulations, that is, the presence of at least two background stimuli preceding each word, an SOA of 250 ms, and the use of an average-reference method (as reported in Martın-Loeches et al, 2001a) would guarantee a remarkable RP. Even so, it seems clear from this study that not all the mentioned manipulations are required simultaneously Thus, if RP is a potentially relevant component in the study of semantic manipulations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only is RP better seen in parietooccipital leads, but its distribution is indeed limited to that region, its amplitude largely decaying as we move from PO7 or PO8 (see, for instance, Martın-Loeches et al, 2001a). Curiously, thesé electrodes are quite scarcely used in ERP research, where the mean number of electrodes used is not usually larger than 20, and neither PO7 nor PO8 have been included.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rate of stimulus presentation in the procedure (normally, the stimulus onset asynchrony [SOA] of each stimulus is 250 ms) is able to force the participants to process the stimuli with their full attention and to attenuate the contamination of irrelevant variables in the electrophysiological signals of interest 16 . It has been suggested that the RP is linked to the pre-semantic processing of words and that it is particularly related to the processing of semantic categorical features 17, 18 . Several groups of moral researchers have proposed in their work that the early stage of the temporal dynamics in moral judgment may involve a rapid and intuitive “right-or-wrong” categorization process 5, 6, 10 .…”
Section: Introductionmentioning
confidence: 99%